2021
DOI: 10.18196/jmmr.v10i2.10378
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Strengthen Mental Health Services in Hospital during Covid-19

Abstract: Psychiatric disorders that arise due to Covid-19 include anxiety, depression, psychological trauma and the use of drugs to deal with tension caused by the pandemic. A total of 535 respondents (49%) out of 2,364 respondents had thoughts about death. Hospitals must make changes and mitigate, accelerate and adapt faster. This article aims to identify best practice strategies for suicide prevention to improve mental health services in hospitals. This study used queries: "suicide prevention", "covid" and "hospital"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…The previous study found that resilience is related to nurses’ ability to adapt to workplace challenges and minimize the negative effects of occupational demands [ 51 ]. A study conducted in one of Indonesia’s public hospitals found that nurses there have high resilience, reaching 90.4% [ 52 ]. Nurses with high resilience can help them respond to workplace stress and complex conditions [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The previous study found that resilience is related to nurses’ ability to adapt to workplace challenges and minimize the negative effects of occupational demands [ 51 ]. A study conducted in one of Indonesia’s public hospitals found that nurses there have high resilience, reaching 90.4% [ 52 ]. Nurses with high resilience can help them respond to workplace stress and complex conditions [ 53 ].…”
Section: Discussionmentioning
confidence: 99%